PENGARUH VARIASI KECEPATAN TERHADAP LEBAR HAZ DAN NILAI KEKERASAN MATERIAL PADA PROSES PEMOTONGAN STAINLESS STEEL SUS 304 DENGAN MENGGUNAKAN PLASMA CUTTING - Haris, Emin (Universitas Muhammadiyah Metro, 2024)
Plasma cutting is often used in the industrial world, because this process is more effective and efficient in its users, therefore this cutting process must be considered material properties and cutting methods based on function and purpose. In this study, cutting used plasma cutting, the cutting speed variation method used for SUS 304 stainless steel. The speed variations used are 0.0045 m/s, 0.0252 m/s, 0.0470 m/s. Then it is tested by micro and hardness testing. In this observation, the best speed was obtained at the third variation of 0.0470 m / s because it had the smallest average HAZ width value of 427.83 μm and the highest average material hardness value of 167.753 Kg.f. For the largest average HAZ width was found in the first variation of 0.0045 m / s which was 1240.33 μm and the smallest material hardness value was found in the second variation of 0.0252 m / s which was 163.76 Kg.f.